Analysts: No doubt PKR a party with Malay roots - News Straits, Times (New Straits Times, 2014)
KUALA LUMPUR: Analysts agree with the assertion that PKR is a Malay based party as stated by its secretary-general Datuk Saifuddin Nasution Ismail.They also concurred that PKR deputy president Azmin Ali's rebuttal of the fact was only made in the vein of the party's aspiration to turn it into a multiracial political platform.